A guide to teaching information literacy 101 practical tips - Blanchett, Helen (Facet Publishing, 2012)
This easy-to-use book is an invaluable source of inspiration for any librarian involved in teaching information literacy, whether they are new to teaching or experienced but in search of fresh ideas.